Pendidikan Akhlak Dalam Perspektif Filsafat Pendidikan Islam - Saputri, Nurul; Lestari, Rani Endah; Sirait, Nilna Mayang Kencana (TARBIYAH: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Education in the view of Islam is an effort made to prepare humans to have awareness, ability, and obligation to carry out the mission of caliph. this research uses qualitative research methods that aim to describe completely and in depth about the nature of Ethical Education in the View of Islamic Education Philosophy. The result of his research is that in education, important efforts are directed at developing the potential of human nature, so that after arriving at this development, he is able to play himself in accordance with the nature he carries, and is able to do good to the Creator. Development here is expected as a description of the ideal level of development achieved by each potential human nature.